The rural landscape - Hart, John Fraser (Johns Hopkins University Press, 1998)
"In this book, John Fraser Hart offers a comprehensive handbook to understanding the elements that make up the rural landscape--those regions that lie at or beyond the fringes of modern metropolitan life. Though the last two centuries have seen an inversion in the portion of people living on farms to those in cities, the land still beckons, whether traversed in a car or train, scanned from far above, or as the locus of our food supply or leisure. The Rural Landscape provides a deceptively simple method for approaching the often complex and variegated shape of the land. Hart divides it into its mineral, vegetable, and animal components and shows how each are interdependent, using examples from across Europe and America. Looking at the land forms of southern England, for instance, he comments on the use of hedgerows to divide fields, the mineral or geomorphological features of the land determining where hedgerows will grow in service of the human animal's needs. Hart reveals the impact on the land of human culture and the basic imperative of making a living as well as the evolution of technical skills toward that end (as seen in the advance of barbed wire as a function of modern transportation). Hart describes with equal clarity the erosion of land to form river basins and the workings of a coal mine. He charts shifting patterns of crop rotation, from the medieval rota of food (wheat or rye), feed (barley or oats), and fallow (to restore the land) to modern two-crop cycle of corn and soybeans, made possible by fertilizers and pesticides. He comments on traditions of land division (it is almost impossible to find a straight line on a map of Europe) and inventories a variety of farm structures (from hop yards and oast houses to the use of dikes for irrigation). He identifies the relict features of the landscape--from low earthen terraces once used in the southern United States to prevent erosion to old bank buildings that have become taverns and barns turned into human homes. Carrying the story of the rural landscape into our frantic era, he describes the'bow wave'where city life meets rural agriculture and plots the effect of recreation and its structures on the look of the land."--